Evaluation of the Implementation and Impact of the My School My Pesantren Program at State Elementary School 1 Karangmangu in the 2024/2025 Academic Year - Ari Dwi Atmojo; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
Evaluation of the Worship Practice Program which is integrated into one program of my school, my Islamic boarding school at Elementary School 1 Karangmangu aims to provide an assessment of the implementation and achievement of program objectives. The Stufflebeam CIPP model is used in the study to evaluate the context aspects (objectives, guidance, and implementation), input aspects (materials, teachers, and students), process aspects (program implementation techniques), and products or outputs (results). The analysis of the research data used a descriptive qualitative approach. The data collection tool used observation to assess teacher behavior by students, self-assessment questionnaires by students, and student behavior assessment questionnaires by parents. The objects of the study were 8 teachers, 41 students, and 41 parents of students. The evaluation results showed that the context and input aspects were in the good category. The process evaluation was in the good category, related to the implementation time and steps for implementing PSP activities in accordance with the established guidelines. The product evaluation was in the sufficient category, meaning that individually students could be said to be quite good in religious behavior. While the assessment of religious behavior indicators showed in the good category.